ESG Ratings, Agency Cost and Corporate Performance: The Case of Chinese Firms in 2009-2023 - Yuefeng Xu; Shuangao Wang; Tiezheng Wang; Qintao Fan; Michael Chak Sham Wong (Sustainable Futures)
This study investigates the intricate relationship between Environmental, Social, and Governance (ESG) ratings and corporate performance among 3,100 Chinese A-share firms from 2009 to 2023, emphasizing the mediating role of agency costs. Utilizing return on assets (ROA) as a key measure of financial performance, our analysis demonstrates that higher ESG ratings correlate with improved corporate outcomes, particularly when agency costs are low. The findings remain robust across various control variables, including company size, financial ratios, and board structure. By integrating Stakeholder Theory and Agency Theory, this research reveals that strong ESG practices not only enhance corporate reputation and stakeholder trust but also improve governance, aligning management interests with those of shareholders. The identification of agency costs as a critical mediating factor provides fresh insights into how Chinese firms can effectively leverage ESG initiatives for superior financial results. These results hold significant implications for corporate leaders and investors, highlighting the necessity of effective governance structures to optimize the financial benefits of sustainability practices in emerging markets.